(untitled) (The Research of Medical Science Review, 2025)
The sudden rise in the number of human immunodeficiency virus (HIV) outbreaks in District Dir Lower, Pakistan, is a serious issue for the local population, and hospitals of the area. The first official case of HIV in Pakistan was reported in the year 1987. Since then, the number of people living with HIV in the country has increased significantly. According to the data mentioned by UNAIDS, in the year 2023, approximately 290,000 individuals including both adults and children are living with HIV in Pakistan.